KEMAMPUAN KOMITEN ORGANISASI MEMODERASI KOMPETENSI DAN KEJELASAN SASARAN ANGGARAN PADA AKUNTABILITAS KINERJA PERGURUAN TINGGI NEGERI PARIWISATA - Setyawati, Ni Putu Ayu Nirvana; Ratnadi, Ni Made Dwi; Widanaputra, A.A.G.P; Gayatri, Gayatri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022, 2022)
This study was conducted to discuss Performance Accountability in State Tourism Universities (PTNP). The purpose of this study is to prove organizational commitment as a moderating variable has an effect on the competence of government officials and the clarity of budget targets on performance accountability. The population in this study were six (6) State Tourism Universities (PTNP). The sampling method used non-probability sampling. The selected respondents consisted of Director/Chairman, Deputy Director/Assistant Director, Head of Section, Head of Subdivision, Head of Department, Head of Study Program, Head of Research and Community Service Center, and Head of Quality Assurance Unit so that the number of respondents was 105 respondents. The data used in the form of primary data using a questionnaire distributed using whattsapp with google form media. The analysis technique used is Moderated Regression Analysis. The results of the study indicate that organizational commitment moderates the effect of government apparatus competence and clarity of budget targets on the accountability of the performance of State Tourism Universities